The play-along method: An ethnographic approach to analyze video game culture - Steinnes, Kamilla Knutsen; Maunsah, Henry; Reich, Clara Julia (AoIR Selected Papers of Internet Research, 2026)
Online gaming platforms constitute unique field sites for researching different themes related to digital youth culture such as play, learning, socialization, and consumption. However, they pose methodological challenges for sociocultural digital media research. This paper introduces the $2 method, inspired by the 'media go-along', “scroll back” and 'app walkthrough' techniques, which involves the informant logging onto and playing a game in the presence of the researcher while they engage in a discussion about aspects of the game that unfold on the screen. By observing and participating in gameplay, researchers gain insights into player agency, game mechanics, and consumption practices within virtual worlds. Carried out across three research projects involving 60 young informants aged 10-24, the method offers several advantages: immersion in the gaming context, and a flexible, informal interview setting. It provides a unique opportunity to observe real-time interactions, digital purchases, relevance of devices, affordances and design, and relational dynamics. However, the method also presents challenges, such as gameplay interference, parental restrictions, and technical issues. Ethical considerations include maintaining the privacy of third parties and managing the blurred boundaries between the informant's private and research contexts. Despite these challenges, the play-along method represents a significant methodological advancement for studying virtual worlds. It underscores the need for child-centered approaches that acknowledge the relationalities between players and digital infrastructures, and map unexplored digital terrain in video games. The method's participatory nature positions informants as experts in their own lives, providing rich, authentic insights into the commercial and social dimensions of online gaming.